Training and 24-hr urinary catecholamine excretion - Filaire, E.; Rouveix, M.; Duclos, M. (International Journal of Sports Medicine, 2009)
We examined the effects of 28 weeks of training on 24-hr urinary catecholamine excretion and mood (evaluated using the Recovery-Stress Questionnaire for Athletes RESTQ-Sport) among seven national young female tennis players. Data were collected after a 1-month rest (September, T1), 3 months after T1 (T2) and 7 months after T1 (T3). Standardized Stress and Standardized Recovery scores and RESTQ-Index were computed. The training load increased by 161 % between T1 and T2 and by 55 % between T2 and T3. The performance (wins/total number of matches) decreased throughout the study. Urinary catecholamine excretion presented an U-shaped curve with a significant increase in 24-hr urinary catecholamine excretions, and epinephrine/norepinephrine ratio from T1 to T2 (T1 vs. T2: epinephrine: + 100 %, p < 0.05; norepinephrine: + 30 %, p < 0.05. Then, at T3, urinary catecholamine excretions and the epinephrine/norepinephrine ratio decreased significantly to values lower than the values observed at T1. A decrease in RESTQ-Index throughout the study was mainly based on a large increase in the Standardized Stress score. Changes in specific stress and recovery scales of the RESTQ-Sport for athletes and changes in catecholamine values indicated a state of heavy training stress and incomplete recovery at the end of the study.